Effect of Feeding Noodle Waste on Growth Performance of Calves - Dhakal, Birendra (Journal of the Institute of Agriculture and Animal Science, 2024)
The insufficient supply of good quality feed in developing countries is the main limiting factor of livestock production, which accounts for approximately 70% of the investment in feed. Owing to the high cost of feed, farmers in Bhutan are unable to provide good quality feed to livestock; as a result, animals do not perform as needed. Some farmer heifers reach their body weight only at three years of age, which is supposed to reach 55 % of mature body weight 1t 13-15 month of age. Therefore, it is necessary to find good alternatives to locally available feed resources to address this gap and reduce investment in heifer production. This study was conducted at Dorokha, where 18 calves were fed noodle waste for 12 weeks to evaluate the growth performance of the calves. The Experimental animals were assigned to three groups T1 (normal diet plus 0.5 kg of noodle per calf per day), T2 (normal diet plus 1 kg of noodle per calf per day) and C (maintain only on a normal diet), through stratified random selection method with a completely randomized design (CRD). ANOVA was conducted to examine weight gain among the treatment groups (C, T1 and T2) and significant differences in weight gain were detected, F (2, 1) = 28.247, P<.05. In contrast the weight gain in the T1and T2 treatments was significantly greater than that in the control (C), t (213) =8.579, p<.05. The ADG of the control was 0.160 kg, that of T1 was 0.39 kg, and that of T2 was 0.43kg. Independent t test revealed that the average weight gain of the Yangku and Yangkum breeds was significantly greater than that of the Siri breed in yearling calves.